Effect of different inter-stimulus intervals (ISI) on Cortical Auditory Evoked Potential in normal hearing adults: a pre-liminary findings - Abdul Rahim, 'Afaf Ezzaty; Dzulkarnain, Ahmad Aidil Arafat (IIUM Press, International Islamic University Malaysia, 2018)
The aim of this study was to investigate the effect of different inter-stimulus intervals to the Cortical Auditory Evoked Potential (CAEP) findings in adult participants. Nineteen normal hearing individuals aged between 20 and 24 years old participated in this study. CAEP were measured by presenting 1000 Hz tone burst stimulus at 70dBnHL at three different inter-stimulus intervals (ISI)s of 2000, 909 and 555 ms in randomized order. Results revealed significant changes in the CAEP’s amplitude as a function of ISI with a reduction of P1-N1 amplitude of up to 50%. N2 peak was absent in some subjects using short ISI (555 ms). This study concluded that the use of very short ISI (e.g. 555 ms) may not be appropriate clinically because it can reduce the CAEP wave amplitude and can cause an absence of peak N2. In contrast, the use of short ISI may be useful for other clinical applications that may benefit from neural habituation and refractoriness, for example to predict the potential future outcome of speech and mental disorders.